Model Pelaksanaan Pembelajaran Pendidikan Agama Islam dengan Sistem Moving Class Dalam Meningkatkan Motivasi dan Prestasi Belajar Siswa SMP IT Sahabat Alam - Muhammad Tri Ramdhani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Moving classes is teaching and learning systems that provide a new atmosphere in the learning process. This system is characterized by the moved class where students will move in accordance with the scheduled subjects. The concept of moving class refers to a student-centered learning and provides a dynamic environment in accordance with what they learn. It is very influential to the development of education in an effort to improve the quality of human life. The results of this study showed that according to the writer’s observation and study, SMP IT Sahabat Alam has not implemented yet the learning system that based on moving class learning that requires it has its own classroom space for each subject. But the school has its own unique characteristics and the learning system is to be based on a natural learning system that is suitable to the material. In addition, SMP IT Sahabat Alam has several activities that are of Islamic education include learning the Qur’an, Qur’an Night, Tadabur Alam, all of them still have a link to the learning of Islamic education that is done out of the class and class hours.